Management of Adverse Events Following Treatment With Anti-Programmed Death-1 Agents. (8th July 2016) - Weber, Jeffrey S.; Postow, Michael; Lao, Christopher D.; Schadendorf, Dirk
Abstract : Immune checkpoint inhibitors have emerged as a mainstay of melanoma therapy and are playing an increasingly important role in the treatment of other tumor types. The clinical benefit afforded by these treatments can be accompanied by a unique spectrum of adverse events, called immune-related adverse events (irAEs), which reflect the drug's immune-based mechanism of action. IrAEs typically originate in the skin, gastrointestinal tract, liver, and endocrine system, although other organ systems may also be affected. This article provides an overview of irAEs associated with anti-programmed death-1 (anti-PD-1) antibodies (nivolumab and pembrolizumab) as monotherapy or in combination with anti-cytotoxic T-lymphocyte antigen-4 inhibition (ipilimumab), followed by a discussion of irAEs of special clinical interest based on the potential for morbidity, frequent steroid use, and inpatient admission. We review clinical trial data and provide recommendations on how to manage irAEs associated with anti-PD-1 agents based on clinical experience and established management guidelines. We further illustrate the practical considerations of managing irAEs by presenting three cases of immune-related toxicity in melanoma patients treated with nivolumab or pembrolizumab. A better understanding of the identification and management of irAEs will help inform health care providers about the risks associated with anti-PD-1 treatment, to ensure the safe and appropriate use of these important new treatments. Abstract : This review focuses on the management of immune-related adverse events (irAEs) after treatment with anti-programmed death-1 antibodies as monotherapy or in combination in patients with advanced melanoma. A better understanding of the management of irAEs will help ensure the safe and appropriate use of these agents in melanoma and other tumor types.